2015
DOI: 10.1371/journal.pcbi.1004169
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Predicts IGFBP2-HIF1α Interaction Drives Glioblastoma Growth

Abstract: Tremendous strides have been made in improving patients’ survival from cancer with one glaring exception: brain cancer. Glioblastoma is the most common, aggressive and highly malignant type of primary brain tumor. The average overall survival remains less than 1 year. Notably, cancer patients with obesity and diabetes have worse outcomes and accelerated progression of glioblastoma. The root cause of this accelerated progression has been hypothesized to involve the insulin signaling pathway. However, while the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 78 publications
(64 reference statements)
1
7
0
Order By: Relevance
“…IGFBP2 expression in the tumor has been proved in many researches that was associated with a variety of pathological conditions, including hypoxia [24] and regeneration [25]. In the present study, we founded IGFBP2 high cells accumulate in the immediate vicinity of focal necrosis of some tumors.…”
Section: Discussionsupporting
confidence: 56%
“…IGFBP2 expression in the tumor has been proved in many researches that was associated with a variety of pathological conditions, including hypoxia [24] and regeneration [25]. In the present study, we founded IGFBP2 high cells accumulate in the immediate vicinity of focal necrosis of some tumors.…”
Section: Discussionsupporting
confidence: 56%
“…Analysis of reverse-phase protein array data (RPPA; a high-throughput antibody-based technique) from the TCGA GBM dataset yielded proteins significantly associated with TREM1, including IFGBP2, TGM2 VEGFR2, and NDRG1, many of which have also been linked to hypoxia ( Figures 5B,G–I ). IGFBP2 has been reported to exert an oncogenic effect by enhancing invasiveness, angiogenesis, and VM formation and as part of a negative feedback loop with HIF1α in glioma ( 24 26 ). It has also been correlated with classic immunosuppressive biomarkers in glioma, such as CHI3L1, TNFRSF1A, LGALS1, TIMP1, VEGFA, ANXA1 , and LGALS3 ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…Downstream signaling from insulin-like growth factor (IGF1) through Ras to HIF-1α upregulates mRNA encoding IGFBP2, thus autoregulating HIF by decreasing IGF1 signaling (Feldser et al, 1999 ; Sinha et al, 2011 ). IGFBP2 is often upregulated in GBM, promoting tumor development, progression, and invasion (Lin et al, 2015 ). Through modeling it was shown that IGFBP2 plays an integral role in sustaining HIF-1α signaling in an oxygen-independent manner due to its negative effect on IGF1 signaling (Lin et al, 2015 ).…”
Section: Hypoxia Inducible Factors and The Tumor Microenvironmentmentioning
confidence: 99%
“…IGFBP2 is often upregulated in GBM, promoting tumor development, progression, and invasion (Lin et al, 2015 ). Through modeling it was shown that IGFBP2 plays an integral role in sustaining HIF-1α signaling in an oxygen-independent manner due to its negative effect on IGF1 signaling (Lin et al, 2015 ).…”
Section: Hypoxia Inducible Factors and The Tumor Microenvironmentmentioning
confidence: 99%